NILAI PERUSAHAAN: KEPUTUSAN PENDANAAN DAN MANAJEMEN ASET - Erawati, Teguh; Sumaningsih, Dwi Astuti (Jurnal Akuntansi, 2025)
This research aims to analyze the influence of Asset Management, Profitability, Dividend Policy and Funding Policy on Company Value. The sample used was manufacturing sector companies listed on the Indonesia Stock Exchange from 2018 to 2021. Using the purposive sampling method, 34 companies were obtained. This research uses multiple linear regression analysis. This research was also carried out with the aim of being a reference for investors in making decisions. The research results show that profitability has a positive effect on company value, funding policy has a negative effect on company value, asset management and dividend policy have no effect on company value.